International organization and global governance (London ;New York : Routledge Taylor & Francis Group, 2014)
"Featuring a strikingly diverse and impressive team of authors, this is the most comprehensive textbook available for courses on international organizations and global governance. This book covers the history, theories, structure, activities and policies
Includes bibliographical references and index.
Keywords: International organization; Uluslararası organizasyon; International agencies; Uluslararası ajanslar; International relations; Uluslararası ilişkiler; Globalization; Küreselleşme